Cancer risk with alemtuzumab following kidney transplantation. (11th March 2013) - Puttarajappa, C.; Yabes, J.; Bei, L.; Shah, N.; Bernardo, J.; McCauley, J.; Basu, A.; Tan, H.; Shapiro, R.; Unruh, M.; Wu, C.
Abstract Alemtuzumab has been employed for induction therapy in kidney transplantation with low rates of acute rejection and excellent graft and patient survival. Antibody induction therapy has been linked to increased vulnerability to cancer. Data regarding malignancy rates with alemtuzumab are limited. We studied 1350 kidney transplant recipients (between 2001 and 2009) at the University of Pittsburgh Starzl Transplant Institute, for post‐transplant de novo and recurrent malignancy, excluding non‐melanoma skin cancer, among patients receiving alemtuzumab, thymoglobulin, and no induction therapies. Of the 1350 patients, 1002 (74.2%) received alemtuzumab, 205 (15.2%) received thymoglobulin, and 122 (9%) received no induction therapy. After excluding cancers occurring within 60 d post‐transplantation, 43 (3.25%) malignancies were observed during a median follow‐up time of 4.0 yr. The incidence of malignancy was 5.4% (1.09 per 100 patient‐years [PY]) with thymoglobulin, 2.8% (0.74 per 100 PY) with alemtuzumab, and 3.3% (0.66 per 100 PY) with no induction (across all groups; p = 0.2342, thymoglobulin vs. alemtuzumab; p = 0.008). Thus, with the exception of non‐melanoma skin cancer which we did not evaluate, alemtuzumab induction was not associated with increased cancer incidence post‐kidney transplantation when compared to no induction therapy and was associated with lower cancer incidence when compared to thymoglobulin.